New Achievements in Geoscience - Lim, Hwee-San (IntechOpen, 2012)
New Achievements in Geoscience is a comprehensive, up-to-date resource for academic researchers in geophysics, environmental science, earth science, natural resource managements and their related support fields. This book attempts to highlight issues dealing with geophysical and earth sciences. It describes the research carried out by world-class scientists in the fields of geoscience. The content of the book includes selected chapters covering seismic interpretation, potential field data interpretation and also several chapters on earth science.